Organic Farming in India: Its Opportunity and Challenges in the Context of Globalization - Chandra, Satish; Shankar, Sowmya (Indian Journal of Marketing, 2007)
Organic farming is a system of crop and livestock production that promotes and enhance the health of agriculture, eco-system and while producing pure and healthy food. The annals of organic farming exist ever since the birth of this godly planet. It was Sir. Albert Howard how was the first man to cultivate organically in India at Pusa, and published the article on organic farming during the year 1900. But the history shows that the presence of organic farming even in the Vedic period, Ramayana and Mahabharata this shows the evidence that there is a practice of organically cultivated lands in India in olden days. But after Sir Albert Howard published his article, a German philosopher Rudolph Steinar builds biodynamic method of organic farming. Later to popularize this concept Europeans developed a guideline called ’Codex’. Approximately 120 countries adopted this guidelines and cultivating organically with an area of 31.1 million ha. Among this countries Australia stands first with 21.1 million ha. Though in India, organic farming is in its relatively old practiced it is not practicing at large. This is mainly due to the challenges and constrains faced in Indian market. But the bigger challenges before organic food is marketing, though the demand for organic product is increasing there is a many major obstacles to the further development of the organic market which need to be removed. To remove these obstacles this paper highlights and focuses on the opportunities and constrains in organic marketing, consumer attitude towards organic goods and policy consideration in developing organic food. Entering this lucrative market is not easy however there is a growing demand for organic food in major urban cities. But organic agriculture is facing major challenges as it is not an automatically an alternative food. It as to go a long way before it zips and zooms.